MAKNA LAGU NENGGO DALAM UPACARA PENTI DI NGKOR, DESA BANGKA LA’O, KECAMATAN RUTENG, KABUPATEN MANGGARAI - Antonia Pendi Mantu; Karolus B. Jama; Aris Nurhuda (Yayasan Panca Bakti Wiyata Pangandaran, 2025)
The focus of this study is to find out the meaning contained in Song called “Nenggo” in ceremony Penti at Ngkor, Bangka La'o village, District Ruteng, Regency Manggarai. The aim of this study is to describe the meaning contained in song “Nenggo” at the Ceremony Penti di Ngkor, Bangka La'o village, District Ruteng, Regency Manggarai. There are two benefits of this study, they area theorical benefits and practical benefits. Theoretically, this study is expected to stimulate and increase the way of thingking or enrich concepts to literature related to Indonesian language specifically in solving problems occurring in society. Whereas practically, the benefits of this study is for the readers, researchers, and investigators. The method used in this study is descriptive qualitative method. Meanwhile, the theory used is semiotics theory (Roland Barthes). The use of semiotics analysis in this study succeed dig meaning deep from everylyrics of the “Rana rembong” song, so can be understood in a way more widely by society in general. The result of this study found that there are 3 meanings of the “Nenggo” song, they are: (1) the denotation meaning consists of erelele: embrace, rembong: protector, rana: lake, mbaru: house, beo: village, wekol: happiness, enggo: jungle cat; (2) the connotative meaning includes erelele: warmly receive, rembong: someone who has high authority, rana: beauty and mystery of nature, mbaru: warmth, security, shelter, beo: simple life and close to nature, wekol: positive feelings, satisfaction and joy, enggo: reflects relationships humans and nature; (3) myth contains erelele: a symbol of strong emotional ties, rembong: a figure who protects and preserves traditions and cultural values, rana: a source of life for various kinds of living creatures, mbaru: a place connected to ancestors or spirits ancient, beo: a symbol of ethnic and cultural identity, wekol: happiness that everyone wants, enggo: a symbol of courage. Thus, “Nenggo” is a traditional song which use in ceremony like penti, caci, birth, and marriage and contains deep meaning as a culture identity and as a medium used to embrace and unite the community in a village. Nenggo „‟Rana rembong‟‟ is not just a song but also as a medium that expresses local wisdom, spirituality, and life social public Manggarai.